2011
DOI: 10.1111/j.1365-2516.2011.02506.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing bleed frequency and factor concentrate use between haemophilia A and B patients

Abstract: Haemorrhagic manifestations in patients with haemophilia A and B are considered quite similar for comparable level of factor deficiency. We investigated the bleeding frequency and factor usage between HA and HB patients with comparable disease severities. We collected data on frequency of bleeds and factor concentrate utilization over 3 years, from January 2001 to December 2003. Information was gathered from home infusion logs recorded by patients or their parents, and treatment records from the Hemophilia Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 8 publications
10
61
3
1
Order By: Relevance
“…Differences in health were statistically significant in six subscales and in the total score; however, a trend to significance ( P = 0.066–0.084) could also be detected to the other subscales (Table 7). This finding is consistent with recent studies, in which higher bleeding frequency has been observed in patients with haemophilia A compared to patients with haemophilia B [40, 41]. …”
Section: Discussionsupporting
confidence: 94%
“…Differences in health were statistically significant in six subscales and in the total score; however, a trend to significance ( P = 0.066–0.084) could also be detected to the other subscales (Table 7). This finding is consistent with recent studies, in which higher bleeding frequency has been observed in patients with haemophilia A compared to patients with haemophilia B [40, 41]. …”
Section: Discussionsupporting
confidence: 94%
“…5,6,23 These studies included between 20 and 35 hemophilia B patients per study and between 68 and 252 hemophilia A patients, and they had conflicting results. Others have examined surrogate outcomes to compare hemophilia A and B.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent data suggest that hemophilia B is associated with a less severe bleeding phenotype than hemophilia A, although the data are inconsistent between studies. [2][3][4][5][6] In a study by den Uijl et al, 7 rates of joint bleeding were found to decrease by 18% for each 1% increase in baseline FA level among 433 Dutch patients with moderate or mild hemophilia A who were receiving on-demand therapy. Limitations of the study were the small number of patients studied, the single data capture point for each patient, and the lack of data from patients with hemophilia B.…”
Section: Introductionmentioning
confidence: 98%
“…[7][8][9] In a previous study, we provided evidence of a strong correlation between the severity of arthropathy in HA patients and the expression of the RANK/RANKL/OPG triad in synovial tissue, as well as circulating levels of sRANKL and OPG. 19 Therefore, in the present work we investigated for the first time the possible differences in the RANK/RANKL/OPG triad between HA and HB patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 More recently, many studies demonstrated a higher use of continuous prophylaxis and greater factor consumption in severe HA patients compared with those with severe HB. [7][8][9][10] Moreover, Tagariello et al, in a retrospective survey of joint arthroplasty in the frame of the Italian Hemophilia Center Association, showed that patients with HA had a 3-fold higher risk of undergoing orthopedic arthroplasty, that is an indirect expression of severity of arthropathy. 11 Finally, Mannucci et al suggested that HB is milder than HA also because of the different expression of the pathogenetic gene defects.…”
Section: Introductionmentioning
confidence: 99%